Phonetics-Based Training in the Pronunciation of the Inflectional -ed Ending: A Pedagogical Intervention Study with EFL Learners - Agung Pranoto Kadiatmaja (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to document and analyse the impact of a pedagogical intervention based on the International Phonetic Alphabet (IPA) on the accuracy of pronunciation of the English -ed inflection among EFL learners with an Arabic language background in the context of Indonesian Islamic higher education institutions (PTII). This qualitative pedagogical intervention study involved 30 participants (N=30) from several universities and institutions selected using purposive sampling. The intervention was conducted in three structured sessions, integrating form-focused instruction (FFI), memorisation techniques, and mnemonic strategies. Data were collected via observation sheets, field notes, and participant testimonials, and subsequently analysed using thematic analysis (Braun & Clarke, 2006). Thematic analysis yielded three main themes: (1) increased metacognitive phonological awareness, (2) increased self-efficacy in pronunciation, and (3) the role of Islamic communicative motivation as a driver of learning engagement. The IPA-based intervention supported by mnemonic strategies proved to be effective and contextually relevant for the population of EFL learners with an Arabic language background at PTII. These findings strengthen the empirical basis for the design of EFL pronunciation curricula.